Strategic Planning in Digital Marketing: Bibliometric and Content Analysis - Irene Kanina Ratih; Muhammad Saad Salahudin; Syarifa Hanoum; Jaroslaw Korpysa (International Journal of Business and Management Technology in Society, 2023)
Purpose – This study is aimed to map the trend, conceptual structure, and characteristic of strategic planning in digital marketing research. Methodology – This study uses Performance Bibliometrics analysis and Science Mapping Techniques. Performance Bibliometrics is used to analyze basic information and Science Mapping Techniques are used to find differences in future studies. the PRISMA method was used to complete the analysis performed. Findings – the most prolific and influential journals, authors, countries, and research dominated by Spain, the United States, and the United Kingdom. In addition, four themes are found that are often used in this field of study, namely the "marketing" cluster, the "decision theory" cluster, the "strategic approach" cluster, and the "social media" cluster. Research limitations – This study only covers research published related to strategic planning in digital marketing, the data selected only use synta strategic, and the co-occurrence analysis was used to present the conceptual structure in this study. Practical implications – This research will help practitioners to understand the basis of job satisfaction in textile factory workers and contribute to the scientific community by providing thematic maps and recommendations for future research of this field of study.